Peningkatan Prestasi Belajar Biologi Siswa Kelas X SMA Negeri 1 Sungai Lilin melalui Metode Proyek dengan Penilaian Prestasi dan Poster - Yanti, Zeni Okta; Juliana, Juliana (Medan Resource Center, 2023)
Implementing the discussion method in studying the topic of Biology, especially in learning about the environment, leaves students unable to apply in real life what they have learned in school. Because of that, in this research, the Project Method through group work was used in the task of recycling organic and inorganic waste. The goal of this research was to enhance the students’ affective, cognitive, and psychomotor ability. The research Project took the form of class action research carried out in two cycles, both of which consisted of planning, implementing, observing, and reflection. The results of the research showed that by implementing the Project Method, the ability of the students increased in all three aspects: the cognitive aspect as evidenced by the daily test scores, the affective aspect as was apparent in the student’s initiative in making posters to raise environmental awareness.